PENINGKATAN PEMAHAMAN PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS DALAM KURIKULUM 2013 MELALUI SIARAN PEMBINAAN BAHASA INDONESIA DI RADIO REPUBLIK INDONESIA SURAKARTA - Rahmawati, Laili Etika; Sufanti, Main; Markhamah, Markhamah; Ngalim, Abdul (WARTA, 2015)
The aims of service on social through the on air broadcast of RRI Surakarta were to: (1) improve the understanding of teachers of Bahasa Indonesia toward the Bahasa Indonesia learning program based on texts; (2) enrich the knowledge of the listeners, especially for the students in which the learning of bahasa Indonesia based on the curriculum 2013; (3) create the close work relation of institution between the Muhammadiyah University of Surakarta and the government instituion i.e. Radio of Indonesian  Republic  of  Surakarta. The  soacial  service  was conducted  in RRI  of Surakarta, in the form of lecturing in an on-air broadcast, based on the paper which had been prepared  before. The on-air broadcast activities were  conducted by the recording before broadcasted. The recording process used the facilities in RRI of Surakarta guided by workers of RRI of Surakarta, both the responsibility and the recording process. The activities were conducted by on-air broaadcast. Every time the on-air broadcast was conducted by the speaker in which the topics were varies but, they were still on one theme. The on-air broadcast theme on the next three month is ?The Improvement of Understanding the Learning of Bahasa Indonesia based on Texts of the Curriculum 2013 through the guiding on-air broadcast of Bahasa Indonesia in RRI of Surakarta?. The six times on-air broadcast activities which planned for three months, could be conducted six times of the new on-air broadcast.